Assessing the carbon sequestration potential of basalt using X-ray micro-CT and rock mechanics. (March 2018) - Callow, Ben; Falcon-Suarez, Ismael; Ahmed, Sharif; Matter, Juerg
Graphical abstract: Highlights: CO2 mineral carbonation storage capacity and reservoir properties of basalt assessed. 3D X-Ray micro-CT image analysis of core samples determine pore network properties. Hydromechanical tests show stress dependency of permeability at reservoir pressures. Calculated CO2 storage capacity of 0.33 Gt CO2 at CarbFix site in Iceland. Secondary mineral pore clogging may reduce CO2 storage capacity of basalt reservoirs. Abstract: Mineral carbonation in basaltic rock provides a permanent storage solution for the mitigation of anthropogenic CO2 emissions in the atmosphere. 3D X-ray micro-CT (XCT) image analysis is applied to a core sample from the main basaltic reservoir of the CarbFix site in Iceland, which obtained a connected porosity of 2.05–8.76%, a reactive surface area of 0.10–0.33 mm −1 and a larger vertical permeability (2.07 × 10 −10  m 2 ) compared to horizontal permeability (5.10 × 10 −11  m 2 ). The calculations suggest a CO2 storage capacity of 0.33 Gigatonnes at the CarbFix pilot site. The XCT results were compared to those obtained from a hydromechanical test applied to the same sample, during which permeability, electrical resistivity and volumetric deformation were measured under realistic reservoir pressure conditions. It was found that permeability is highly stress sensitive, dropping by two orders of magnitude for a −0.02% volumetric deformation change, equivalent to a mean pore diameter reduction of 5 μm. This pore contraction was insufficient to explain such a permeability reduction according to the XCT analysis, unless combined with the effects of clay swelling and secondary mineral pore clogging. The findings provide important benchmark data for the future upscaling and optimisation of CO2 storage in basalt formations.